2019
DOI: 10.1016/j.thromres.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and determinants of whole blood and plasma fibrinolysis in patients with mild bleeding symptoms

Abstract: This is a repository copy of Assessment and determinants of whole blood and plasma fibrinolysis in patients with mild bleeding symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Also, no evidence was found supporting a systemic hyperfibrinolytic capacity in BUC patients. In contrast, we found that clot lysis time was significantly prolonged in BUC patients compared to healthy controls, in line with previously published data, 30,31 hereby carefully rejecting hyperfibrinolysis as underlying pathophysiological mechanism for BUC.…”
Section: Discussionsupporting
confidence: 92%
“…Also, no evidence was found supporting a systemic hyperfibrinolytic capacity in BUC patients. In contrast, we found that clot lysis time was significantly prolonged in BUC patients compared to healthy controls, in line with previously published data, 30,31 hereby carefully rejecting hyperfibrinolysis as underlying pathophysiological mechanism for BUC.…”
Section: Discussionsupporting
confidence: 92%
“…Viscoelastic testing might better represent coagulation in vivo than routine hemostatic assays due to its whole blood dynamic assessment. Assessment of the complete fibrinolytic system remains notoriously difficult, but tissue plasminogen activator rotational thromboelastometry (tPA ROTEM) is thought to be more sensitive to hypofibrinolysis than other clinically used assays (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, another Dutch group, Vries et al, 48 recently did not identify significant differences in clot formation nor clot strength using ROTEM nor differences in a turbidity assay between 240 patients with self‐reported bleeding and 95 patients without bleeding symptoms who were scheduled for an elective surgery. The discrepancies between these studies may be partially explained by the smaller samples sizes in some cohorts, 4,47,48 the heterogeneity of investigated patients, and interlaboratory variations 49 . More specifically, Hofer et al 47 included adult patients with a MBD, who were screened by a hemostasis expert, Veen et al included subjects >12 years old while Vries et al compared patients >18 years old who had one or more self‐reported bleeding symptom before an elective surgery with patients without a self‐reported bleeding manifestation.…”
Section: Hyperfibrinolysis In Bleeding Cohorts and Patients With Bucmentioning
confidence: 98%
“…In contrast, Veen et al 4 recently reported a prolonged clot lysis time in a smaller cohort of 109 patients with BUC compared to healthy controls, and no difference in ROTEM parameters was found. Finally, another Dutch group, Vries et al, 48 recently did not identify significant differences in clot formation nor clot strength using ROTEM nor differences in a turbidity assay between 240 patients with self‐reported bleeding and 95 patients without bleeding symptoms who were scheduled for an elective surgery. The discrepancies between these studies may be partially explained by the smaller samples sizes in some cohorts, 4,47,48 the heterogeneity of investigated patients, and interlaboratory variations 49 .…”
Section: Hyperfibrinolysis In Bleeding Cohorts and Patients With Bucmentioning
confidence: 98%